Image segmentation algorithms and their use on doppler images - Tatiana D. C. A. Silva (2011)
This paper aims to make a review on current segmentation algorithms used for medical images. Image segmentation algorithms can be classified according to their methodologies, namely the ones based on thresholds, clustering, and deformable models. Each type of algorithms is discussed as well as their main application fields identified; additionally, the advantages and disadvantages of each type are pointed out. Experiments that apply the algorithms to segment Doppler images are presented to further evaluate their behaviour.